Analytical and Experimental Investigation of Neutral Point Clamped Quasi-Impedance-Source Inverter - Ott, Silver; Roasto, Indrek; Vinnikov, Dmitri; Lehtla, Tõnu (Electrical, Control and Communication Engineering, 2011)
In this paper a new modification of a three-level neutral-point-clamped inverter is presented. The proposed topology combines the advantages of the three-level neutral-point-clamped full-bridge inverter with those of the quasi-impedance-source inverter. The neutral-point-clamped quasi-impedance-source inverter is especially suitable for renewable energy sources.The steady-state analysis of a neutral-point-clamped quasi-impedance-source inverter in the continuous conduction mode is presented. The presented models as well as deduced equations are verified by an experimental prototype.